Impact of the severity and extension of dental caries lesions on Turkish preschool children’s oral health-related quality of life: a cross-sectional study - Ayça Kurt; Damla Bolat; Ömer Hatipoğlu (BMC Oral Health)
Abstract Background Dental caries is a prevalent oral disease affecting young children, leading to significant negative impacts on oral health-related quality of life (OHRQoL). This study aims to evaluate the relationship between extension of dental caries lesions and OHRQoL in children aged 3–6 years using the Early Childhood Oral Health Impact Scale (ECOHIS). Methods This cross-sectional study involved 300 children aged 3–6 years and their parents or caregivers. Clinical examinations were conducted using the decayed, missing, and filled teeth (dmft) Index, the pufa Index, and the International Caries Detection and Assessment System (ICDAS) II. The ECOHIS was administered through interviews with parents or caregivers to assess the impact of dental caries on OHRQoL. Statistical analyses, including Kruskal-Wallis and binomial logistic regression, were performed to evaluate the relationship between pufa scores and ECOHIS results. Results The findings revealed a significant negative impact of dental caries on OHRQoL (p < 0.05). The mean ECOHIS score was 0.62 ± 0.552, with higher scores observed in children with a pufa Index score > 0 compared to those with a pufa Index score of 0 (p < 0.05). Significant impacts were observed in specific ECOHIS items, such as oral/dental pain (mean score 1.61 ± 1.13), difficulty eating (mean score 1.26 ± 1.26), and trouble sleeping (mean score 0.528 ± 0.942). Parental distress was also notably high, with significant scores in feeling upset (mean score 1.07 ± 1.31) and feeling guilty (mean score 0.929 ± 1.26). Binomial logistic regression analysis showed that a higher pufa score was a significant predictor of increased ECOHIS scores (adjusted OR = 1.929, p = 0.039). The dmft score also significantly predicted higher ECOHIS scores (adjusted OR = 6.597, p = 0.048). Spearman correlation analysis revealed a significant positive correlation between pufa and ECOHIS scores (r = 0.33, p < 0.05). Conclusions The study demonstrates that extension of dental caries lesions, particularly when measured by the pufa Index, significantly impacts specific aspects of OHRQoL, including pain, eating difficulties, and sleep disturbances in children, as well as emotional distress in parents. Early detection and management of dental caries are crucial in improving the quality of life for affected individuals. Dental practitioners should prioritize preventive measures and parental education to mitigate the adverse effects of dental caries.